Waking up every day in a body that is not yours: a qualitative research inquiry into the intersection between eating disorders and pregnancy - Elizabeth A. Claydon; Danielle M. Davidov; Keith J. Zullig; Christa L. Lilly; Lesley Cottrell; Stephanie C. Zerwas (BMC, 2018)
Abstract Background Women with eating disorders are more likely to negatively react to finding out they are pregnant, although this difference in attitudes between women with eating disorders and controls disappears at 18-weeks' gestation. Those with anorexia also are twice as likely to have an unplanned pregnancy and those with bulimia have a 30-fold increased chance compared with healthy controls. Therefore, due to these considerations, pregnancy and the transition to motherhood can be an extremely challenging time for these women both psychologically and physically. The purpose of this qualitative descriptive study was to understand the intersection between eating disorders and pregnancy from the lived experience of women who have been pregnant or want to or do not want to become pregnant. Methods A total of 15 women with a current or past history of an eating disorder were recruited, including nine women who have had previous pregnancies as well as six nonparous women. Interviews were the primary unit of data collection, in addition to document analysis of diaries or blogs. Data analysis was based on verbatim transcripts from audio recordings. NVIVO 11© was used to manage the data from these interviews and thematic analysis was then conducted for emergence of major and sub themes. Results A total of six themes emerged from the iterative process of coding and categorizing. They were: Control, Disclosure to Others, Battle between Mothering & Eating Disorder, Fear of Intergenerational Transmission, Weight and Body Image Concerns, and Coping Strategies. One theme, Battle between Mothering & Eating Disorder also had three sub-themes: Decision to Have Child, Emotions Towards Pregnancy, and Focus on Child/Greater Good. Conclusions It is hoped that quotes and themes derived from this study will help inform both prenatal and postnatal care and interventions, as well as addressing intergenerational transmission concerns among mothers with eating disorders.